Assessment of solar load models for bifacial PV panels - Rasheed, Bushra; Safdar, Asmara; Sajid, Muhammad; Ali, Sara; Ayaz, Yasar (Frontiers in Energy Research, 2022)
Solar load is one of the key inputs in thermal analysis of all solar based applications using ray tracing. Commercial and academic Computational Fluid Dynamics (CFD) codes incorporate different solar load models for ray tracing, i.e., Solar Position and Intensity (SOPLOS) theoretical maximum function, American Society of Heating, Refrigeration, and Airconditioning Engineers (ASHRAE) fair weather and constant solar load models. However, solar load depends largely on weather conditions of the site whereas the solar load models in CFD software do not accommodate changing weather patterns and hence the CFD simulation results obtained are not representative of an extended period of time. This paper studies the effect of changing weather patterns on solar load assessment, using bifacial solar panels as a case study. In this study, on-site data of a humid sub-tropical region for monsoon season, mid-June to mid-August, has been used as an input for solar ray tracing due to large temperature variations and cloud cover for longer duration. Comparative study of SOPLOS and ASHRAE models with in situ model shows that they over predict front side solar load, with only 0.5% and 13% matching in situ data respectively, while both models under predict rear side solar load in the studied time period, with 2% and 24% solar load estimation agreeing with in situ data respectively.